Spectroscopic evidence of multiple populations in globular clusters. (5th March 2015) - Gratton, R.; Lucatello, S.; Carretta, E.; Bragaglia, A.
Abstract: We review spectroscopic evidence of multiple stellar populations in globular clusters. First, we lay down the basic data: the C-N, Na-O, Mg-Al anti-correlations among red giants and main sequence stars, and discuss how they appear to be general properties of globular clusters, in spite of cluster-to-cluster differences. We will then describe what is currently known about He from spectroscopy. We will then present the implications and current observations for the interpretation of the horizontal branches, showing that the multiple population phenomenon is strongly related to the distribution of stars along them. We will briefly mention the spectroscopic evidence related to some less understood cases, like the clusters with multiple subgiant branches. Finally, we summarize the relation between multiple populations and general properties for globular clusters, and their implications for the formation scenario.